Análisis y síntesis de sistemas de ingeniería para la preparación y toma de decisiones bajo criterios múltiples - Arzola Ruiz, José (2002)
We present a methodology for the analysis and synthesis of systems dedicated to the preparation and decisions making under multiple objectives, as well as its application to engineering tasks. This methodology presupposes the realization of the following steps: -decomposition of the task of more spans which belong the studied task,-external and internal analysis, and-elaboration of the general procedure of preparation and decisions making. Examples of application of this methodology to the solution of great complexity engineering tasks are exposed.